2023
DOI: 10.1002/viw.20230001
|View full text |Cite
|
Sign up to set email alerts
|

Cell death mediated by nanotechnology via the cuproptosis pathway: A novel horizon for cancer therapy

Abstract: Cuproptosis, the current form of regulated cell death characterized by copper overload, oligomerization of lipoacylated proteins, and loss of Fe-S cluster proteins, has been proposed to function closely with human diseases, including cancer. Since its first identification in 2022, many strategies have been developed to induce cuproptosis for cancer therapy, such as small-molecule drugs and nanomaterials. Although many reviews related to cuproptosis have been reported, they remain at a basic mechanism level, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Although cuproptosis has shown promising prospects in cancer therapy, there are still some challenges to overcome. For example, how to selectively increase the Cu concentration in cancer cells, and how to precisely target cancer cells to avoid damaging normal cells ( Wei and Fu, 2023 ). Nanomaterials, due to their unique physicochemical properties and biological effects ( Zhong et al, 2022 ), have the potential to address these issues and are currently widely applied in basic research for cancer diagnosis and treatment, with the aim of achieving clinical applications ( Fu et al, 2021 ).…”
Section: Cuproptosis and Cancer Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Although cuproptosis has shown promising prospects in cancer therapy, there are still some challenges to overcome. For example, how to selectively increase the Cu concentration in cancer cells, and how to precisely target cancer cells to avoid damaging normal cells ( Wei and Fu, 2023 ). Nanomaterials, due to their unique physicochemical properties and biological effects ( Zhong et al, 2022 ), have the potential to address these issues and are currently widely applied in basic research for cancer diagnosis and treatment, with the aim of achieving clinical applications ( Fu et al, 2021 ).…”
Section: Cuproptosis and Cancer Treatmentmentioning
confidence: 99%
“…Copper-based nanomaterials can serve as a novel type of cuproptosis inducers, which can achieve active targeting through surface modification, and passively accumulate a large amount of copper at the tumor site through the enhanced permeability and retention (EPR) effect ( Figure 6 ). This ultimately leads to cuproptosis in cancer cells, exerting a therapeutic effect ( Wei and Fu, 2023 ).…”
Section: Cuproptosis and Cancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The proper function of key proteins is often dependent on biological ions, especially the metal ions, such as Ca 2+ , Mn 2+ , Fe 2+/3+ , and so on. These play well-established biochemical and nutritional roles for cellular function, growth, and survival, while the induction of an imbalance of ion content usually results in fetal consequences, even death. , Moreover, ions and their nanomaterials have been revealed in defending the disease progression in part, especially in antitumor treatment. For instance, calcium ion (Ca 2+ ), a kind of essential trace element, has been explored broadly based on its biological roles, including the regulation of intracellular signaling, cellular homeostasis, and immunity of the cell, which thus decides the proliferation, metabolism, and death of various kinds of cells . Under this circumstance, the oscillation of Ca 2+ content could be an efficient method to induce various biological processes, in which the alteration of Ca 2+ content could change the charge properties of phospholipids to promote the activation of T cell receptor and evoke the immune response .…”
Section: Introductionmentioning
confidence: 99%
“…Similar to Ca 2+ , Mn 2+ has also attracted great attention in tumor treatment due to its roles in the enzymatic transformation of TME. Recently, some studies have reported the Mn 2+ can prime the cGAS-STING pathway via different mechanisms to elicit potent innate and adaptive antitumor immunities for effective tumor suppression effectively. , Therefore, Mn 2+ can significantly improve the therapeutic effects of immunotherapy via the reform the TME and the enhancement of immunotherapy. , Moreover, the strategies based on two ions, such as the combination of Ca 2+ , Cu 2+ , Mn 2+ , Zn 2+ , Fe 2+ / 3+ , etc., have been proposed and have shown good therapeutic effects in antitumor treatment. ,,, However, the combination of Ca 2+ and Mn 2+ dual-ion overloading-mediated tumor therapy has rarely been reported in detail.…”
Section: Introductionmentioning
confidence: 99%